La utilización de los cuentos “La caperucita roja” y “Juanito y Margarita” para el desarrollo de las cuatro destrezas comunicativas (audición, habla, escrito, comprensión) de los alumnos del 7º año de la enseñanza fundamental de la escuela Profª Laura dos Santos Ribeiro - PINHEIRO, Nair Figueiredo (2021)
This work is based on observations made in the supervised internship discipline, where we testify in E.E.E.F.M. Prof. Laura dos Santos Ribeiro regarding the E / LE teaching, no literary works were presented in the development of school discipline. Know that literary texts are inserted into the teaching process when learning a language, either in the student's mother tongue or in a foreign language, because it is through it that the student develops his reading competence. We seek to adapt the teaching and learning methods of the Spanish language in primary school and comply with literary aspects in the process of acquiring a language. In addition to encouraging reading in students, we present the use of the Grimm brothers' stories in the E / LE classes, so that when they work literary texts they contribute to developing the communicative skills of a Foreign Language. Therefore, the stories we will use in this proposal are the original versions of the stories "Little Red Riding Hood" and "Juanito and Margarita" by the Grimm brothers written in the target language (Spanish). Such works were chosen because they are quite popular and contain adaptations in children's books and movies. We assume that stories in Spanish have the basic linguistic and literary structural elements to teach an LE. Using works by authors such as Ângela Kleiman, Julio Cortázar, R. Casson, A. Gaignoux, J. W. Geraldi, V. Leffa, and others to compose the theoretical foundation of this work, so that we provide a clear discussion of the subject.